2020
DOI: 10.51791/njap.v44i1.448
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of Citrullus lanatus rinds in male wistar rats

Abstract: Water melon, citrullus lanatus is a common edible fruit belongs to the family of cucumber (Cucurbitacea). The outer part of citrullus lanatus known as the rind is always discarded. This study investigated the effects of ethanol extract of citrullus lanatus rinds orally administered on some liver function enzymes, kidney function markers, cardiac risk ratio, and the atherogenic coefficient indices in male wistar rats. Twenty-five male Wistar albino rats were randomly distributed into five groups (I, II, III, IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…There was hyperproteinaemia in rats treated with 800 and 1600mg/kg CLREF and rats that received 800 and 1600mg/kg CLRCE which is an indication that the CLREF can initiate or enhance good affinity for transporting lipids, vitamins and minerals in the body with improved body immune system (Peng et al, 2020). It can also be inferred that CLRCE will exhibit good affinity for effective cardiovascular system in the body as seen in the study of Akintunde et al, (2017) et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There was hyperproteinaemia in rats treated with 800 and 1600mg/kg CLREF and rats that received 800 and 1600mg/kg CLRCE which is an indication that the CLREF can initiate or enhance good affinity for transporting lipids, vitamins and minerals in the body with improved body immune system (Peng et al, 2020). It can also be inferred that CLRCE will exhibit good affinity for effective cardiovascular system in the body as seen in the study of Akintunde et al, (2017) et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…The extracts of citrullus lanatus seed had been confirmed to possess pharmacological actions such as anti-inflammatory, hepatoprotective and antioxidant activity (Alka et al,2008) The citrullus lanatus fruit had been shown to possess significant anti-hepatotoxic properties (Altas & Kizil, 2011), with high anti-hyperlipidemic (Aruna et al, 2012), antigiardia, anti-inflammatory, anti-secretory, laxative, gastroprotective, anti-ulcerative, antibacterial, antioxidant, antimicrobial and analgesic activities in man and animals (Deshmukh et al, 2015). Citrullus lanatus rind possesses analgesic activity (Kumari et al, 2013); cardioprotective effects (Akintunde et al, 2017). The citrullus lanatus fruit has haematinic effects in rats (Akintunde et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…al., 2016). The watermelon rind had also been investigated and conf irmed to cause cardiovascular system protection (Akintunde et al, 2017;Abu-Hiamed, 2018); Fan et al, 2020) due to the presence of phytochemicals constituents.…”
Section: Cardioprotectivementioning
confidence: 99%
“…The Citrullus lanatus rind (CLR) is edible and used as a vegetable in meals7 this is emphasizing the nutritive values found in it. The Citrullus lanatus rind possesses cardio-protective effects8 with the presence of some antioxidant's compounds. Moreover, fruits of CL have been shown to cause antipyretic and anti-inflammatory effects3 .…”
mentioning
confidence: 99%